Covid-19 has caused a dramatic change to prison life’: analysing the impacts of the Covid-19 pandemic on the pains of imprisonment in the Scottish Prison Estate - Maycock, Matthew (The British journal of criminology, 2022)
The purpose of this paper is to provide insights into the impact of COVID-19 in the Scottish Prison Estate. During the 2020 lockdown in prison in response to the COVID-19 pandemic, all face-to-face research was paused. In response to this methodological challenge, a participatory correspondence methodology was designed, enabling project participants to influence the direction of this project through suggesting research questions. The main project findings relate to the analysis of ways in which the COVID-19 enhanced the pains of imprisonment for participants, exploring the challenges that the participants faced in relation to communication, feelings of heightened isolation and detachment from family, friends and the normal rhythms of life in prison. Analysis of the letters received as part of this study provides unique insights into the ways in which the COVID-19 pandemic in custody has added an additional layer or enhancement to pre-pandemic pains of imprisonment, increasing the ‘tightness’ ‘depth’ and ‘weight’ of participants time in custody.